Walking in Quicksand:: An exploration of trainee’s experience of a five day residential training workshop - Evans, Ken (European Journal for Qualitative Research in Psychotherapy, 2014)
Between June 26 to 30th, 2013, sixteen Integrative psychotherapy trainees attended a five day residential training workshop to introduce them to qualitative research. The trainees were half way through the third year of a four year training programme run by the European Centre for Psychotherapeutic Studies, which is a European accredited training institute of the European Association for Psychotherapy and a Full Train- ing Member of the European Association for Integrative Psychotherapy. This was the second residential workshop for the trainees following their first experience of one in June 2012, during their second year of training. The workshop was on this occasion primarily facilitated by Dr Ken Evans who has a particular interest in phenomenological and relational oriented research in and with groups (Finlay and Evans, 2009).